Factors of decisive importance for being in work or not during two years after breast cancer surgery: content analysis of 462 women's open answers - Agneta Wennman-Larsen; Veronica Svärd; Kristina Alexanderson; Emilie Friberg (BMC, 2021)
Abstract Background Paid work is one of the most important aspects in life among working-aged women diagnosed with breast cancer. Despite several attempts, no previous study provides a comprehensive overview from the women's perspective about factors of importance for being able to work or not. Therefore, the aim of this study was to gain knowledge about factors that women themselves state are of decisive importance for being able to work or not during the first two years after breast cancer surgery. Methods Data was collected in a two-year follow-up questionnaire within the frame of a prospective cohort study of working-aged women who had undergone breast cancer surgery. 749 were included in the questionnaire study and of the 616 (82%) responding women, 462 (75%) wrote statements on an open-ended question about factors of decisive importance for being able to work or not work during the past two years. The statements were analyzed with content analysis. Results Five categories of factors of importance for being able to  work or not were identified, each covering several sub-categories: Health and wellbeing, Contacts and encounters, Flexibility and adjustment possibilities, Socioeconomic consequences from working/not working, and Own motivation and characteristics. A wide variety of factors were mentioned by the women and the findings give a multifaceted picture of many single but interrelated factors of decisive importance for being able to work/not work. The importance of flexibility in the return-to-work process was stressed, as well as the importance of supportive encounters from, e.g., colleagues, managers, as well as relatives. Conclusions The results give a comprehensive overview over a variety of different types of factors for being able to return to/remain in work or to not work after breast cancer surgery, adding new knowledge about e.g. the importance of colleagues, and the women's own preferences or characteristics. These are factors that different stakeholders, both from healthcare but also from the work place and the insurance office, need to be aware of and collaborate around to support women with breast cancer during the period of treatment, rehabilitation and return to work.